Premenstrual symptoms and dysmenorrhea in women using ovulation and menstruation mobile apps - Ozturk, Simge; Sener Cetin, Nurdilan (Taylor & Francis Inc, 2025)
In this study, we aimed to determine premenstrual symptoms and dysmenorrhea symptoms in women using ovulation and menstruation mobile applications. We conducted this study as descriptive and correlational with 730 women. We collected online using the personal information form, Premenstrual Syndrome Scale (PMSS) and Visual Analoque Scale (VAS). In addition, it was determined that as the VAS severity increased in dysmenorrhea, women's use of menstruation mobile application increased (p < 0.05). In addition, as the mean scores of PMSS irritability, pain, and bloating subscales increased, it was determined that the status of using menstruation mobile application increased (p < 0.05). We found that as both dysmenorrhea and premenstrual symptoms increased, the use of menstruation mobile application increased. Our findings suggest that women with dysmenorrhea and premenstrual syndrome use menstruation mobile applications more.
Keywords: Young-Women